Let Juwan's number be represented by \( x \). According to the problem, we can translate the statement into an equation. The phrase "Twice the sum of Juwan’s number and 12" can be expressed as \( 2(x + 12) \), and "four less than three times Juwan’s number" can be expressed as \( 3x - 4 \).
Setting these two expressions equal to each other gives us the equation:
\[ 2(x + 12) = 3x - 4 \]
Now, let's solve for \( x \):
- Distribute on the left side:
\[ 2x + 24 = 3x - 4 \]
- Move the \( 2x \) to the right side:
\[ 24 = 3x - 2x - 4 \]
- Simplify:
\[ 24 = x - 4 \]
- Add 4 to both sides:
\[ 24 + 4 = x \]
\[ x = 28 \]
Thus, Juwan's number is \( \boxed{28} \).